2007
DOI: 10.1111/j.1525-1438.2007.00909.x
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node in endometrial cancer

Abstract: The aim of this study was to evaluate the possibility of identifying the sentinel lymph node and involvement of neoplastic cells in patients with endometrial carcinoma limited to the uterus, and also its correlation with the conditions of other pelvic and para-aortic lymph nodes. Forty patients with endometrial carcinoma, clinical staging I and II, were submitted to complete surgical staging through laparotomy, as recommended by FIGO in 1988. The sentinel node was investigated using patent blue dye in the myom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 19 publications
2
25
0
3
Order By: Relevance
“…The primary goal of SLN in EC consists in reducing the morbidity of a full lymphadenectomy (by decreasing surgical time), as well as early (need of blood transfusion, fever, wound infection, thromboembolism [10]) and late complications (lymphocysts formation, leg lymphedema, transient neuralgias [3,6,[8][9][10][11][12][13][14]). Besides, SLN allows an accurate exploration of all drainage routes as well as those considered aberrant or not routinely examined [12]. It is suggested that SLN could have a value in isolated PA metastatic node detection.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The primary goal of SLN in EC consists in reducing the morbidity of a full lymphadenectomy (by decreasing surgical time), as well as early (need of blood transfusion, fever, wound infection, thromboembolism [10]) and late complications (lymphocysts formation, leg lymphedema, transient neuralgias [3,6,[8][9][10][11][12][13][14]). Besides, SLN allows an accurate exploration of all drainage routes as well as those considered aberrant or not routinely examined [12]. It is suggested that SLN could have a value in isolated PA metastatic node detection.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the use of more sensitive techniques for SLN detection could better identify pelvic nodes and probably reduce the reported incidence of isolated infra-renal metastasis [8]. The secondary goal is to improve detection of micrometastasis, which is associated with a recurrence risk [13], with resource to ultra-sectioning and immunohistochemestry (IHC) protocols [3,6,[8][9][10][11][12][13]. Therefore, the risk of recurrence related to positive lymph nodes missing despite a full lymphadenectomy could be reduced [12], and SLN could improve selection of patients for adjuvant therapy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This situation is clearly different from other viscera, such as the lung and oesophagus [20], mammary gland [26] and stomach [16,23]. Thus, application of sentinel node biopsy for carcinomas of the uterus [11,12] appeared to precede descriptions of normal adult anatomy of the lymphatic drainage routes. Likewise, to our knowledge, no or few studies have demonstrated the LVs around the normal uterus using D2-40 immunohistochemistry, in contrast to the extensive accumulation of knowledge of D2-40-positive LVs in other normal viscera (e.g., oesophagus [34], prostate [6], kidney [9] and others [7]).…”
Section: Introductionmentioning
confidence: 99%